Lowering of cholesterol bioaccessibility and serum concentrations by saponins: in vitro and in vivo studies. Issue 2 (5th December 2014) - Vinarova, Liliya; Vinarov, Zahari; Atanasov, Vasil; Pantcheva, Ivayla; Tcholakova, Slavka; Denkov, Nikolai; Stoyanov, Simeon
Abstract : Quillaja saponaria and Sapindus trifoliatus extracts decrease cholesterol bioaccessibility during in vitro digestion and lower serum cholesterol in mice. Abstract : Using an in vitro digestion model, we studied the effect of six saponin extracts on the bioaccessibility of cholesterol and saturated fatty acids (SFAs). In the absence of saponins, around 78% of the available cholesterol was solubilized in the simulated intestinal fluids. The addition of two extracts, Quillaja Dry (QD) and Sapindin (SAP), was found to decrease cholesterol bioaccessibility to 19% and 44%, respectively. For both extracts, the main mechanism of this effect is the displacement of cholesterol molecules from the bile salt micelles, leading to formation of cholesterol precipitates that cannot pass through the mucus layer of the intestine. QD decreased strongly the SFA bioaccessibility as well, from 69 to 9%, due to formation of calcium-SFA precipitates, while SAP had no effect on SFA. We studied the in vivo activity of QD and SAP extracts by measuring serum cholesterol in mice fed with experimental diets within a 7-day period. Both extracts were found to prevent dietary hypercholesterolemia in mice fed on a cholesterol-rich diet. The other saponin extracts did not show any significant effect in vitro and, therefore, were not studied in vivo . The cholesterol lowering ability of Sapindin extract is reported for the first time in the current study.